The Modern Venus Dress, Underwear and Accessories in the late 18th-Century Atlantic World - Achermann, Simone 1977- (Bloomsbury Visual Arts, 2023)
From rumps and stays to muffs and handkerchiefs, underwear and accessories were critical components of the 18th-century woman's wardrobe. They not only created her shape, but expressed her character, sociability, fashionability, and even political allegiances. These so-called ephemeral flights of fashion were not peripheral and supplementary, but highly charged artefacts, acting as cultural currency in contemporary society. The Modern Venus highlights the significance of these elements of a woman's wardrobe in 1770s and 1780s Britain and the Atlantic World, and shows how they played their part in transforming fashionable dress when this was expanding to new heights and volumes. Dissecting the female silhouette into regions of the body and types of dress and shifting away from a broad-sweeping stylistic evolution, this book explores these potent players within the woman's armoury. Marrying material, archival and visual approaches to dress history, and drawing on a rich range of sources - including painted portraiture, satirical prints, diaries, memoirs - The Modern Venus unpacks dress as a medium and mediator in women's lives. It demonstrates the importance of these overlooked garments in defining not just a woman's silhouette, but also her social and cultural situation, and thereby shapes our understanding of late 18th-century life. With over 125 color images, The Modern Venus is a remarkable resource for scholars, students and costume lovers alike
Keywords: Electronic books